2018
DOI: 10.5858/arpa.2017-0265-ra
|View full text |Cite
|
Sign up to set email alerts
|

Double-Equivocal HER2 Invasive Breast Carcinomas: Institutional Experience and Review of Literature

Abstract: Context.— HER2 status is a prognostic factor and therapeutic target in invasive breast carcinomas. Reflex testing using an alternate method is recommended on equivocal cases via immunohistochemistry or fluorescence in situ hybridization (FISH). Therapeutic dilemmas arise when both tests are equivocal. The standard chromosome 17 centromere reference probe (CEP17) is in close proximity to the HER2 locus and may be coamplified, leading to equivocal results. Alternate chromosome 17 reference prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…9 Several subsequent studies showed that the new equivocal category and the use of alternative chromosome 17 probes resulted in an increase in the proportion of equivocal and amplified HER2 FISH results, particularly among cases with equivocal (2+) IHC results and CEP17 CNA. [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] However, copy number variations also have been reported for the most commonly used alternative chromosome 17 control probes [i.e., RAI1, LIS1 (PAFAH1B1), RARA, and TP53]. 16,17 Therefore, it is not clear which probe provides the most accurate reflection of the chromosome 17 copy number and ultimately the most accurate HER2:control ratio.…”
Section: Discussionmentioning
confidence: 99%
“…9 Several subsequent studies showed that the new equivocal category and the use of alternative chromosome 17 probes resulted in an increase in the proportion of equivocal and amplified HER2 FISH results, particularly among cases with equivocal (2+) IHC results and CEP17 CNA. [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] However, copy number variations also have been reported for the most commonly used alternative chromosome 17 control probes [i.e., RAI1, LIS1 (PAFAH1B1), RARA, and TP53]. 16,17 Therefore, it is not clear which probe provides the most accurate reflection of the chromosome 17 copy number and ultimately the most accurate HER2:control ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, additional copies of CEP17 detected by ISH may be caused by amplification of the centromeric region due to the proximity of the CEP17 gene to the HER2 gene, 103 prompting the use of a centromeric probe or an alternate probe to correct the absolute HER2 copy number to help refine the threshold of HER2 positivity. 104,105 HER2 low positivity: About 40-50% of breast cancer patients are HER2 low, i.e. they are IHC 1+ or 2+ but HER2 gene amplification was negative.…”
Section: Casementioning
confidence: 99%